Intestinal Barrier Repair‐Based Copper‐Kaempferol Nanocomplexes Regulates Gut‐Liver Axis Homeostasis - Weiqi Li; Ping Wang; Wanyue Fu; Yue Li; Jie Zhang; Yechun Jiang; Lingling Xu; Huaze Dong; Haisheng Qian; Wanni Wang (Advanced Healthcare Materials, 2026)
ABSTRACT Inflammatory bowel disease (IBD) and its frequent hepatic complication, metabolic‐associated steatohepatitis (MASH), are intrinsically linked through the dysregulated gut‐liver axis, with intestinal barrier dysfunction serving as a central pathological driver. Coordinated therapy that restores barrier integrity and interrupts pathogenic gut‐liver crosstalk remains a significant challenge. To address this, a colon‐targeted delivery system based on sodium alginate microspheres is developed for loading copper‐kaempferol nanocomplexes (CuK@SA). Upon oral administration, this system prolongs the retention and release of CuK NCs in the colon. Through scavenging reactive oxygen and nitrogen species (ROS/RNS), regulating macrophage polarization, improving microbial homeostasis, and enhancing tight junction protein expression, it multi‐dimensionally restores intestinal barrier integrity and effectively blocks the translocation of endotoxins to the liver via the gut‐liver axis. In mouse models of dextran sulfate sodium (DSS)‐induced colitis and high‐fat‐diet‐induced MASH, CuK@SA significantly alleviates intestinal inflammation, repairs barrier structure, and simultaneously improves hepatic steatosis and inflammatory responses. This work provides a novel strategy for synchronously targeting IBD and its systemic complications through modulation of the gut‐liver axis.